The Magic of Rogues : Necromancers in Early Tudor England - Klaassen, Frank F.; Wright, Sharon Hubbs; Wright, Sharon Hubbs, 1963- (Book collections on Project MUSE., 2021)
In 1510, nine men were tried in the Archbishop's Court in York for attempting to find and extract a treasure on the moor near Mixindale through necromantic magic. Two decades later, William Neville and his magician were arrested by Thomas Cromwell for having engaged in a treasonous combination of magic practices and prophecy surrounding the death of William's older brother, Lord Latimer, and the king. In The Magic of Rogues, Frank Klaassen and Sharon Hubbs Wright present the legal documents about and open a window onto these fascinating investigations of magic practitioners in early Tudor England. Set side by side with sixteenth- and seventeenth-century texts that describe the sorts of magic those practitioners performed, these documents are translated, contextualized, and presented in language accessible to nonspecialist readers. Their analysis reveals how magicians and cunning folk operated in extended networks in which they exchanged knowledge, manuscripts, equipment, and even clients; foregrounds magicians' encounters with authority in ways that separate them from traditional narratives about witchcraft and witch trials; and suggests that the regulation and punishment of magic in the Tudor period were comparatively and perhaps surprisingly gentle. Incorporating the study of both intellectual and legal sources, The Magic of Rogues presents a well-rounded picture of illicit learned magic in early Tudor England. Engaging and accessible, this book will appeal to anyone seeking to understand the intersection of medieval legal history, religion, magic, esotericism, and Tudor history.